SYSTEMIC THINKING AS A PLATFORM FOR MODELING HOTEL AND RESTAURANT CORPORATIONS AS COMPLEX SYSTEMS - MIZJUK, BOHDAN; BARNA, MARTA; MELNYK, IRYNA; TRUT, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Modern challenges from the market necessitate an innovative search for the implementation of effective approaches, methods and technologies of effective business in such a complex socio-economic system as the hospitality industry. Achieving the set goals and obtaining the desired business results, carried out by corporate governance, require an appropriate methodological framework. Its creation requires deep knowledge, understanding of the circumstances and conditions of business, creative use of existing theoretical developments, organizational principles of management, search for effective technologies, use of communication and psychological skills. All of the above is a systematic thinking, which applies to managers of all levels of management, and all staff of the organization. The formation and application of systems thinking is an important means of creating an effective methodology for doing business with socio-economic systems in difficult conditions of a rapidly changing environment. This article presents theoretical theses that address ways to find approaches to the methodology of functioning of complex social systems. Since the structures that ensure the functioning of the hospitality sector are socio-economic, and their activities take place in difficult market conditions, which requires the ability to survive and compete, there is a need for methodological provisions to ensure effective operation. The beginnings of such provisions were developed in the generality of systems theory (JTS) in the twentieth century. Their content and significance remain relevant at this time, when there is an acceleration of change and conditions of doing business. In the field of hospitality, taking this into account requires a certain methodological basis for running a successful business. It is emphasized that the development of a sound methodology is related to the systematic thinking that should be possessed by those involved in the development and implementation of such a methodology. From the theoretical calculations of systems theory, the main provisions that form systems thinking are identified and briefly described. Further research should be aimed at a more detailed and specific disclosure of the four provisions set out in the article and their use in the formation of research methodology in the field of business of hotel and restaurant corporate structures.